Grandmothers matter: how grandmothers promote maternal perinatal mental health and child development - Riem, Madelon M. E.; van der Straaten, Merel (Frontiers in Psychology, 2024)
Low social support has been identified as a risk factor for maternal perinatal mental health problems.However, previous studies have predominantly focused on general social support or support from the partner, often overlooking the roles of grandparents. This mini review discusses recent developments in perinatal health research showing that supportive grandparents may constitute a protective factor against the development of maternal perinatal mental health problems. In addition, we will discuss how grandparental support may promote fetal and child health. The mini review concludes with a call for more research on the role of grandparents in perinatal health. Recognizing grandmothers as collaborators in maternal and child health may afford more effective perinatal health programs and clinical practice, thereby reducing the risk of adaptational and developmental problems.